Forging the ideal educated girl : the production of desirable subjects in Muslim South Asia - Khoja-Moolji, Shenila, 1982- (Islamic Humanities., 2018)
"In Forging the Ideal Educated Girl, Shenila Khoja-Moolji traces the evolving politics of educational reform and development campaigns in colonial India and Pakistan. She challenges the prevailing common sense associated with calls for women's and girls' education by arguing that such advocacy is not simply about access to education but, more crucially, is concerned with molding girls into the kinds of subjects needed to advance societal projects such as nation building, modernization, and solidifying religious identity. Such concerns are often driven by material and cultural struggles for power. Thus, discourses around education for girls and women are sites for the construction not only of gender identity but also of class, religion, and the nation"--Provided by publisher